Pelatihan Manajemen Konflik Dalam Upaya Pencegahan Kekerasan Bagi Siswa SMA Di Kota Palembang - sari mutiara aisyah (Jurnal Serambi Abdimas, 2023)
This community service aims to identify and understand teenagers' perspectives regarding the definition of conflict and types of conflict as well as the importance of building relationships of mutual trust in minimizing conflict as an initial stage that must be mastered in determining what conflict management strategies will be implemented in an effort to encourage the choice of conflict management of constructive methods such as role playing and Forum Group Discussion (FGD) to avoid the use of violence. This service consists of three stages, from planning, program implementation and program evaluation. Through this program, all service participants have understood how to present, improve and develop communication skills in building trust and constructive conflict transformation